Application of current sensor based on giant magnetoresistance effect in distribution network. (October 2019) - Xu, A D; Li, L C; Li, P; Wang, Z M; Wu, Z B; Hao, C J
Abstract: Advanced sensing and measurement techniques are key technologies to realize a smart grid. With the advantages of having a high sensitivity, high linearity, small volume, and simple structure, the giant magnetoresistance (GMR) current sensor has broad application prospects in smart grid measurement and monitoring. This paper presents and studies a current sensor terminal based on giant magnetoresistance chip, the overall structure of the current sensor is designed, the power supply scheme and wireless communication scheme are formulated, the insulation protection and IP protection scheme of the current sensor are designed, and the current sensor terminal which can be used in the distribution network scene is prepared. The field response is carried out in the 10kV distribution transformer cable at last. The stability and reliability of the terminal operation are verified. The research results show that the current sensor developed in this paper has the advantages of convenient layout, stable operation and wireless communication. It can provide more comprehensive and real-time information support for the operation of distribution network and lay the foundation for the transparency of smart grid.